2016
DOI: 10.15390/eb.2016.6095
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions versus Realities: Teaching Quality in Higher Education

Abstract: KeywordsThe purpose of this study is to investigate the perceptions of both students and faculty members on teaching quality in higher education, taking nationality, gender, GPA and faculty members' perceptions of university priorities into consideration. The mixed method approach was used to collect both quantitative and qualitative data simultaneously in the study. The quantitative data were collected from two countries: The United States and Turkey through a questionnaire developed for the study. Qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
2
3
0
3
Order By: Relevance
“…However, it was revealed that these aspects cannot be functionally and effectively used to enable students to acquire the necessary skills in real life. Similar result was emphasized by Ustunluoglu (2016Ustunluoglu ( , 2017. The reports conducted by Hénard ( 2010) highlight that universities should put more effort into developing quality teaching, with an emphasis on pedagogy enhancement, support for student learning, and continuing education for faculty members.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, it was revealed that these aspects cannot be functionally and effectively used to enable students to acquire the necessary skills in real life. Similar result was emphasized by Ustunluoglu (2016Ustunluoglu ( , 2017. The reports conducted by Hénard ( 2010) highlight that universities should put more effort into developing quality teaching, with an emphasis on pedagogy enhancement, support for student learning, and continuing education for faculty members.…”
Section: Discussionsupporting
confidence: 81%
“…It was found that the students and academicians have different opinions. A similar result was identified by Ustunluoglu (2017Ustunluoglu ( , 2016. In similar two studies, the researcher compared the perceptions of the students and academicians involved in the faculties of education of one university in Turkey and one university in Slovakia; and one university in Turkey and one university in the USA with regard to the qualities of teaching methods, classroom management, and assessment-evaluation activities implemented in the lessons.…”
Section: Policies To Improve Teaching In Higher Educationsupporting
confidence: 58%
See 1 more Smart Citation
“…The students' assessment has also become a priority method because, as many sources have pointed out, the teaching performance can be measured at the student level as the direct recipient of teaching (Steinberg & Garrett, 2016). Ustünlüoğlu (2016) suggested that a measure of the academic success or degree expectancy of a university should be taken into account in order to provide an in-depth analysis of the findings in other variables, including ethnicity, gender, and average grade point. The quality of the education would improve through an emphasis on the student needs and desires, a comparison of the teaching staff's performance and competencies, and the development of good higher education assessment systems.…”
Section: The Transition Of Teaching Quality From Traditional Education To E-learningmentioning
confidence: 99%
“…Asimismo, repercuten en la manera de concebir el nuevo papel que deben cumplir tanto las universidades como instituciones encargadas de impartir cultura. Se requiere entonces que las universidades capaciten de manera permanente a sus docentes en el ámbito pedagógico y humanístico para que puedan adquirir las habilidades que potencien el aprendizaje de los estudiantes (García, 2017;Quiroz & Franco, 2019;Üstünlüoğlu, 2016). Si bien los estudios inciden en la capacitación de los docentes, de pasar de una enseñanza empírica a una sistematizada, se debe tener en cuenta la implementación de un proceso de evaluación eficaz del desempeño docente que pueda verificar la validez de los resultados (Escudero, 2019).…”
Section: Introductionunclassified